ANALISIS KINERJA KELOMPOK TANI DALAM PELAKSANAAN PROGRAM HUTAN KEMASYARAKATAN (HKm) DI DESA KATONGAN, KECAMATAN NGLIPAR, KABUPATEN GUNUNGKIDUL - , TAMIMI TILMASANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest is a source of life for the community, especially communities around the forest. On the other hand, the forest should maintained itâs sustainability. Farmers group is one of the important element in supporting the successful implementation of community forest program. This study aims to determine the capacity and performance of KTHKm Wono Rejo, the factors that affect the performance of KTHKm Wono Rejo and efforts should be made to improve KTHKm Wono Rejo performance of the implementation of community forest program. This research was conducted in Katongan village, Nglipar Subdistrict, Gunungkidul Regency, precisely at pot 37 BDH Karangmojo which is reserved for the production of forest community for social forestry. This study uses a quantitative approach with a survey method. Data collecting of data is done by direct observation, interviews and document research. The technique of collecting sample is done by using purposive sampling